Modification, characterization and formulation of Arabic gum hydrogel and microgel as drug carrier / Sani Mamman Ibrahim - Sani Mamman , Ibrahim (2021)
Hydrogels and microgels prepared from natural and synthetic polymers continue to attract the interest of medical and pharmaceutical researchers due to their tunable properties by modifying their molecular structure through derivatization, cross-linking or grafting method. This work aimed at developing Arabic gum modified hydrogels and microgels as smart and stimuli-responsive materials for drug delivery applications. The molecular structure of Arabic gum was modified by graft polymerization process with a monomer methacrylic acid or polymers such as polyethylene glycol dimethacrylate and polyethylene imine respectively. The monomer and polymers of the hydrogels were successfully crosslinked using N, N’-methylenebisacrylamide, the process was initiated by free radical generated from ammonium persulfate and catalyzed by N, N’, N”, N’”-tetramethylenediamine as an accelerator. Chemically modified Arabic gum microgels were prepared by emulsion polymerization system using Tween20 as surfactant and hexane as the solvent. The modifying agents such as methacrylic acid, polyethylene glycol dimethacrylate and polyethylene imine were successfully cross-linked using N, N’-methylenebisacrylamide and precipitated using plenty acetone. Physico-chemical methods of characterization such as Fourier transform infrared, differential scanning calorimetry and X-ray diffraction were used to analyzed and confirmed the successful synthesis of the chemically modified hydrogels and microgels. The surface morphology of the hydrogels and microgels were observed using Field emission scanning electron microscope which shows the presence of network structure and porosity arrangements. The hydrogel yield, gel content and gelation time were found to depend solely on the composition proportions while the microgel size depends on the concentration of surfactant and modifying agents. The mechanical properties increase as the synthetic monomer and polymers concentration increases in the formulation. In response to pH hydrogels containing methacrylic acid swells more in higher pH and less in lower pH, while hydrogels containing polyethylene glycol dimethacrylate and polyethylene imine swelled more in lower or acidic pH and a lower swelling ratio was observed in higher pH solutions. The swelling of hydrogels also depends on the compositions of the swelling medium. The presence of ions in the medium reduces the swelling ratio for the modified hydrogels. The swelling kinetics of chemically modified Arabic gum hydrogels were found according to a non-linear second-order rate equation. The microgels particle size and zeta potentials were varied depending on the modifying agents. Quercetin as a model hydrophobic drug was successfully encapsulated in the hydrogels through direct synthesis method and the in-vitro release was study under pH 1.2 and 7.4. The microgels were encapsulated with doxorubicin through the swelling method and the in-vitro release was studied through a dialysis under condition of pH 4.2 and 7.4. The results confirm the potentials of chemically modified hydrogels and microgels in the application such as drug carrier for targeted delivery.